2020
DOI: 10.1177/2151459320916947
|View full text |Cite
|
Sign up to set email alerts
|

Financial Implications for the Treatment of Medicare Patients With Isolated Intertrochanteric Femur Fractures: Disproportionate Losses Among Healthier Patients

Abstract: Introduction: With an aging American public, the rising incidence of geriatric hip fractures provides a significant impact on the financial sustainability for hospitals. To date, there is little research comparing reimbursement to hospital costs for geriatric hip fracture treatment. The purpose of this study is to compare hospital costs to reimbursement for patients treated surgically with an isolated intertrochanteric femur fracture, insured by the Center of Medicare and Medicaid Services (CMS). Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Similar conclusions can be found in the literature for other diseases [27]. In one study regarding the treatment of intertrochanteric femur fractures, there was a net pro t for treating more comorbid patients but a net de cit for treating healthier patients [28]. Likewise, our results also showed that patients in DRG-2 (with comorbidities) had higher margins per patient than those in DRG-1 (without comorbidities).…”
Section: Discussionsupporting
confidence: 90%
“…Similar conclusions can be found in the literature for other diseases [27]. In one study regarding the treatment of intertrochanteric femur fractures, there was a net pro t for treating more comorbid patients but a net de cit for treating healthier patients [28]. Likewise, our results also showed that patients in DRG-2 (with comorbidities) had higher margins per patient than those in DRG-1 (without comorbidities).…”
Section: Discussionsupporting
confidence: 90%
“…Although this strategy allowed for more valid statistical conclusions and illuminated potential future studies that can be more targeted, more studies consisting of individual chart review to more accurately assess costs and outcomes at varying institutions that participate in the bundle. For example, Kelley et al 25 demonstrated this by doing a cost analysis on 278 individual patients that all had a similar intertrochanteric femur fracture at a single level 1 trauma center. They found that there indeed was a problematic and non-sustainable financial imbalance between the cost of highly comorbid patients and CMS reimbursements.…”
Section: Discussionmentioning
confidence: 99%
“…1 This incidence is increasing, creating a financial burden on the healthcare system, which has been estimated at $6 billion USD per year. [2][3][4][5][6][7][8] Surgical management continues to be the mainstay of treatment for IT fractures, with surgical implants and techniques evolving over the past 2 decades.…”
mentioning
confidence: 99%